Taller reciclaeduca para desarrollar la psicomotricidad en niños de 3 años de la I.E N° 211 - 2018 - Olivares Barreto, Jessica Judith (2019)
This research entitled: "RECICLAEDUCA WORKSHOP TO DEVELOP PSYCHOMOTRICITY IN CHILDREN OF 3 YEARS OF THE N ° 211-2018", allowed the children of the aforementioned Educational Institution to improve the level of psychomotor skills as demonstrated by Results obtained after the application of our research._x000D_ The research is of the applied type, quasi-experimental design, whose population was constituted by the children attending and enrolled in the year 2018 in the classroom of 3 years "A", obtaining a sample population of 13 girls and 11 children out of a total of 24 children._x000D_ The data collection instrument that was used was an observation guide validated to expert judgments, built by the authors to obtain the level of psychomotor development of children, which was structured as follows: 8 dimensions (tonic control postural, balance, dynamic coordination, visomotor coordination, spatial orientation, lateral preference, respiratory control, relaxation); Each dimension had two and three items that were scored with the following score (1, 2, 3), in the end we obtained as a result that the level of development was as follows: From 19 to 31.7: Low level, from 31, 7 to 44.2: Medium level, from 44.2 to 57: High level._x000D_ Therefore, it was concluded that the RECICLAEDUCA Workshop did influence the development of the level of psychomotor skills of 3-year-old children “A” of the “IE-N ° 211-2018” in which it is denoted that there is a significant difference of 95.8%.